Between Ethnocentrism and Multiculturalism: The Cultural Landscape in Polish Guidebooks to Vilnius (1856–1939) and Zalmen Szyk's Toyznt yor Vilne - Degler (Lisek), Joanna (Colloquia, 2021)
This article explores changes over time in the manner in which multiculturalism in Vilnius was shown and evaluated in tourist guidebooks written between 1856 and 1939. It provides an overview of narratives which serves as a background reflecting the uniqueness of Zalmen Szyk’s Yiddish-language publication Toyznt yor Vilne (1939). From the mid-19th century on, one can detect an increasingly strident nationalist patriotism in Polish-language books of this genre, underscored by ethnocentrism and nationalistic megalomania. The city is depicted in most of these guidebooks as a bastion of Polish spirit and martyrdom, the quintessential example being a guidebook published by Juliusz Kłos in 1923. Zalmen Szyk, on the other hand, evinces a much greater readiness to incorporate various models of historical memory and interpretations of urban space: Vilnius in his work is unashamedly multicultural, without a trace of ethnocentrism. Szyk is extremely meticulous and unprejudiced in his treatment of all the ethnic groups living in the city and the heritage they left behind. He writes about each group in turn: Lithuanians, Poles, Ruthenians, Tartars, Germans and Jews, and the adherents of Catholicism, Judaism, Orthodoxy, Protestantism and Islam are all accounted for. In comparison with the Polish-language guides, Szyk’s Yiddish guide to multicultural Vilnius contains by far the most comprehensive description of the Polish cultural presence; notably, he does not shy away from incorporating elements of the romantic model of Polish martyrdom.
Keywords: Vilnius city guides; Zalmen Szyk; Adam Honory Kirkor; Juliusz Kłos; multiculturalism; ethnocentrism